1238 Incidence of Cerebral Palsy in Preterm Born Children Did not Change Since 2004. (October 2012) - Daalen, FV van; Stremmelaar, EF; Bos, AF
Abstract : Introduction: During the last decade survival rates of preterm children continuously improve. It is under debate whether this influences the incidence of cerebral palsy (CP). Objective: To determine changes in incidence of CP and motor disorders in preterm children since 2004, and to identify associated factors. Methods: We included all infants born < 32 weeks, admitted to our tertiary NICU, born in 2004–2005 (period-I) and in 2008–2009 (period-II). We excluded children transferred from other tertiary NICUs, with major malformations, and neuromuscular disorders. We compared the incidence of CP and other motor disorders at the age of 2 years. To identify potential risk factors, we used the Nursery Neurobiologic Risk Score (NBRS), including pH, ventilation, infection, convulsions, intraventricular hemorrhage, periventricular leukomalacia, and hypoglycemia. Results: 558 children were included; 269 period-I and 289 period-II. The incidence in CP was not significantly different: 5.6% vs 6.6%, respectively. The number of children with other motor disorders was significantly higher in period-I than in period-II: 15 vs 5 (5.6% vs 1.7%, p < 0.05). NBRS-scores were median 2.5 vs 2.0 ( p =0.12). In period-I, pH and infection contributed more to a higher NBRS, whereas mild periventricular leukomalacia did in period-II (all p < 0.05). Total and subscores of the NBRS were strongly related to CP ( p < 0.01), apart from hypoglycemia in both periods, and ventilation and suspected infections in period-I. Conclusions: Since 2004, the incidence of CP in preterm children did not change, but rates of other motor disorders decreased, without considerable changes in associated risk factors.